DEFECTIVE AGREEMENTS IN FINTECH DIGITAL DEBT AND RECEIVABLE DEALS - Anggie Karunia; Ekawati; Maisyarah; Fatimah Asyari (Awang Long Law Review, 2026)
This study examines the flawed agreement of will in digital fintech debt agreements by placing Article 1321 of the Civil Code as the basis for assessing the validity or invalidity of agreements in electronic contracts. This normative juridical legal research uses a statutory, conceptual, and, where relevant, case-based approach, by examining the Civil Code, LPBBTI regulations (including POJK 40 of 2024), the Personal Data Protection Law, as well as doctrine and literature regarding defects of will and abuse of circumstances. The results of the study indicate that digital fintech agreements are, in principle, still subject to the valid conditions of an agreement in Article 1320 of the Civil Code, so that the elements of agreement and the provisions on defects of will in Article 1321 remain applicable in technology-based contractual relationships. However, the textual formulation of Article 1321, which only mentions error, coercion, and fraud, does not explicitly cover modern forms of inequality that arise in the relationship between fintech platforms and debtors, such as urgent financial needs, standard digital contracts, information asymmetry, and economic dependence. In this context, the doctrine of abuse of circumstances (misbruik van omstandigheden) is relevantly positioned as a form of defects of will that allows for the cancellation or adjustment of an agreement when the debtor's consent is obtained through exploiting a weak or pressing situation. Strengthening sectoral regulations through POJK 40 of 2024 and personal data protection norms have indeed improved governance standards and administrative protection, but have not replaced the role of free will analysis in contract law. Therefore, this study concludes that Article 1321 of the Civil Code needs to be interpreted dynamically by incorporating abuse of circumstances as a basis for defective will in digital fintech agreements, in order to strengthen legal protection for debtors as the weak party in the technology-based financial ecosystem.